A decision model to determine class III milk hedging opportunities - Holt, Travis J. (Kansas State University, 2007)
Fluid raw milk has become one of the largest agricultural commodities, as measured by gross sales, produced in the United States. Since the federal government began to loosen its control over dairy prices in the early 1980’s, farm level milk prices have seen dramatic increases in volatility. Further, shrinking profit margins are requiring more and more dairy farmers to carry a significant amount of debt. Because of the greater leverage in the industry and reduced government support, many producers desire to find mechanisms by which to reduce price risk. Class III milk futures began trading in 1996 with an objective to provide dairy industry players with a means to reduce price risk by transferring that risk to other market players or speculators. Numerous strategies have been proposed for dairy producers to use in price risk reduction that industry participants both support and denounce. One of the objectives of this thesis was to list and analyze a select number of these strategies for their risk-reducing features. Many of these systematic strategies result in lower risk, but the mean Class III price that results from their use was significantly different depending on the strategy used. Another objective of this thesis was to develop a model-based hedging strategy for Class III milk. Six models were developed to predict the Class III Milk price six months and three months into the future. The results of these models were then compared to the Class III Futures price being offered on the first trading day of the month, six months and three months prior to the production month to be priced. If the futures price was higher, a hedge was initiated. If the futures price was lower, no hedge was initiated and the cash market was used. The decision models developed and tested in this thesis not only reduced price volatility, they also increased the mean Class III price obtained as compared to a “cash-only” strategy. While the decision models were successful in-sample, their out-of-sample testing proved to be considerably less successful as all of the model-based strategies underperformed the cash market. The final area researched by this thesis was that of milk price basis. Basis, as it concerns milk prices, is extremely difficult to predict since it involves both physical milk characteristics and government controlled pricing components. While the predictive models tested gave insight into basis prediction, a clear predictive basis model was not found.
Keywords: Agriculture; Cheese pricing; Dairy; Hedging; Milk pricing; Agriculture, General (0473); Business Administration, General (0310); Economics, Finance (0508)